Is There J-Curve Phenomenon and Asymmetric Effects of Exchange Rate on Trade Balance in East Java? - Rizki Pertiwi; Syamad (East Java Economic Journal, 2024)
This study aims to analyze the effect of exchange rate asymmetry on the trade balance between East Java Province and the largest trading partner countries (China, Japan, and the United States) in the short-run and long-run and to detect the J-Curve phenomenon. This study uses the Nonlinear Autoregressive Distributed-Lag (NARDL) method with 2010Q1 - 2023Q1 time-series data. The results of the study show that in the short-run, both the appreciation (NEG) and depreciation (POS) of the exchange rate have no effect on East Java's trade balance in all models. However, in the long-run, exchange rate appreciation and depreciation have a significant negative effect on East Java's trade balance across all models. Based on the estimation results, it can be concluded that there is no J-Curve phenomenon in East Java's trade balance with trading partner countries. Because in the asymmetry model, the J-Curve phenomenon can occur if depreciation or appreciation has a significant positive effect and is cointegrated in the long-run, regardless of the short-run coefficient being positive or negative and significant or not significant. From these conditions, it can be concluded that the trade industry in East Java is called inelastic. That is, price changes do not affect demand for export and import volumes. Therefore, the policy of depreciating the Rupiah exchange rate is not the best strategy to be implemented as an export promotion for East Java because only a few sectors benefit.